No Household Left Behind : Afghanistan Targeting the Ultra Poor Impact Evaluation - Bedoya, Guadalupe (World Bank, Washington, DC, 2019)
The share of people living in extreme poverty fell from 36 percent in 1990 to 10 percent in 2015 but has continued to increase in many fragile and conflict-affected areas where half of the extreme poor are expected to reside by 2030. These areas are also where the least evidence exists on how to tackle poverty. This paper investigates whether the Targeting the Ultra Poor program can lift households out of poverty in a fragile context: Afghanistan. In 80 villages in Balkh province, 1,219 of the poorest households were randomly assigned to a treatment or control group. Women in treatment households received a one-off "big-push" package, including a transfer of livestock assets, cash consumption stipend, skills training, and coaching. One year after the program ended -- two years after assets were transferred -- significant and large impacts are found across all the primary pre-specified outcomes: consumption, assets, psychological well-being, total time spent working, financial inclusion, and women's empowerment. Per capita consumption increases by 30 percent (USD 24 purchasing power parity, USD 7 nominal per month) with respect to the control group, and the share of households below the national poverty line decreases from 82 percent in the control group to 62 percent in the treatment group. Using modest assumptions about consumption impacts, the intervention has an estimated internal rate of return of 26 percent, excluding non-monetized improvements in psychological well-being, women's empowerment, and children's health and education. These findings suggest that "big-push" interventions can dramatically reduce poverty in fragile and conflict-affected regions.